Food‐induced fatal anaphylaxis: From epidemiological data to general prevention strategies. Issue 12 (26th November 2018) - Pouessel, Guillaume; Turner, Paul J.; Worm, Margitta; Cardona, Victòria; Deschildre, Antoine; Beaudouin, Etienne; Renaudin, Jean‐Marie; Demoly, Pascal; Tanno, Luciana K.
Summary: Background: Anaphylaxis hospitalizations are increasing in many countries, in particular for medication and food triggers in young children. Food‐related anaphylaxis remains an uncommon cause of death, but a significant proportion of these are preventable. Aim: To review published epidemiological data relating to food‐induced anaphylaxis and potential risk factors of fatal and/or near‐fatal anaphylaxis cases, in order to provide strategies to reduce the risk of severe adverse outcomes in food anaphylaxis. Methods: We identified 32 published studies available in MEDLINE (1966‐2017), EMBASE (1980‐2017), CINAHL (1982‐2017), using known terms and synonyms suggested by librarians and allergy specialists. Results: Young adults with a history of asthma, previously known food allergy particularly to peanut/tree nuts are at higher risk of fatal anaphylaxis reactions. In some countries, cow's milk and seafood/fish are also becoming common triggers of fatal reactions. Delayed adrenaline injection is associated with fatal outcomes, but timely adrenaline alone may be insufficient. There is still a lack of evidence regarding the real impact of these risk factors and co‐factors (medications and/or alcohol consumption, physical activities, and mast cell disorders). Conclusions: General strategies should include optimization of the classification and coding for anaphylaxis (new ICD 11 anaphylaxis codes), dissemination of international recommendations on the treatment of anaphylaxis, improvement of the prevention in food and catering areas, and dissemination of specific policies for allergic children in schools. Implementation of these strategies will involve national and international support for ongoing local efforts in relationship with networks of centres of excellence to provide personalized management (which might include immunotherapy) for the most at‐risk patients.